(3QSGdI aj JaSjQ bhdg JYGdi (B" (3df JfGdhG GdHQ(B"s
(3ChdgG (B:s
(3GdMeO ddg GdPi aQfG eG jhUd Edi HQg HdSGf GdbQGf hgj bhdg JYGdi (B( (3df JfGdhG GdHQ MJi JfabhG eeG JMHhf (B) (3MjK EMJXi ef YGe GfYGeg cd Zfi habjQ s
(3BNQgG (B:s
(3hMGUdg Cf eG jUdM dJYdb GdbOQI ZjQ eJfGg heG hLO agh eJfGg bWYkG gPG eG JjSQ HYhf Gdgd JYGdi hGdMeO ddg QH GdYGdejf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3djOf s
Keywords: (3GdJaSjQ hYdhe GdbQBfs